Effects of tobacco smoking on cardiovascular disease in patients with systemic lupus erythematosus: A systematic review and meta-analysis - Zhang, Wan-tong; Liu, Zhao; Zhu, Bao-chen; Cui, Zi-yang; Huang, Cheng; Wang, Xu-jie; Lu, Fang; Li, Qiu-yan; Weng, Wei-liang; Hua, Guo-dong; Xue, Chun-miao (Frontiers in Immunology, 2022)
Background: Patients with systemic lupus erythematosus (SLE) are at increased risk of cardiovascular disease (CVD) compared to the general population. However, little is known about the effects of tobacco smoking on CVD in patients with SLE. Objective: To systematically review and summarize the available literature regarding the effects of tobacco smoking on developing CVD in patients with SLE. Methods: We retrieved relevant studies from the following databases: PubMed, EMBASE, Web of Science and China National Knowledge Internet (CNKI) database. Two reviewers independently reviewed the eligible studies, assessed their validity, and extracted relevant data. Sensitivity and subgroup analyses were performed to distinguish sources of heterogeneity. Results: A total of 10 studies, which comprised 6984 participants, were included in the analysis. The overall quality of evidence was rated as moderate to low. The smoking prevalence among CVD patients was 39.28% (271/690), which was higher than 31.36% (1974/6294) among non-CVD patients. Compared with never-smokers, the risk of developing CVD in current smokers was 1.42 (95% CI: 1.21–1.66). No significant publication bias was found in our meta-analysis. Conclusions: In spite of the several negative results, this study found that current smokers with SLE have an increased risk of developing CVD, although most of the included studies were in low-to-moderate quality.